Normative Mechanisms in the Papua Special Autonomy Policy Implementation Network - Kareh, Yakob; Sukri, ‎; Ibrahim, Muh Akmal (KnE Social Sciences, 2025)
Papua Special Autonomy (Otsus) is a policy with strategic value in the context of improving services, accelerating development, and empowering all people in Papua. In the policy implementation network, normative mechanisms are needed as a basis for the policy network. This study aims to analyze the normative mechanism in implementing the Otsus policy. Qualitative research methods were used in this study. Data collection methods include observation, in-depth interviews, and documentation. Data sources consisted of primary and secondary data, while data analysis was conducted using interactive methods. The informants in this research are stakeholders who are directly involved in the implementation of the Otsus policy. The results of research on the implementation of Otsus policy show that normative mechanisms play an important role in shaping the behavior of actors in the policy network. In addition to normative rules such as regulations and standard operating procedures, cultural values and Papuan customary norms are also a reference in the implementation of affirmation programs. The implementation network is formed through collaboration between the local government, the Papuan People’s Assembly (MRP), and the community. However, there is often a conflict between customary norms and values and the formal government bureaucracy.